RELATIONSHIP BETWEEN SELF-EFFICACY AND SELF-REGULATED LEARNING WITH ACADEMIC ACHIEVEMENT IN THE FACULTY OF PSYCHOLOGY, UNIVERSITY OF SURABAYA - Sari, Dessy Annastia (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
In the world of education, at every level of education, whether at elementary school (SD), Junior High School (SMP), Senior High School (SMA) and a College (PT), academic achievement is a measure of the achievement of the learning outcomes. At the college level, academic achievement demonstrated by achievement index (IP). GPA is a number that indicates a persons achievement in learning or work. High academic achievement is the expectation of all students, but in reality not all students have high academic achievement. The phenomenon of low academic achievement occurs in some students of the Faculty of Psychology at University of Surabaya. These results because their lack of ability to manage their time for study and they also have belief that they are less capable to cope with the difficulties that they found in terms of achievement at future. The purpose of this research was to determine the relationship between self-efficacy and self-regulated learning with academic achievement. The population of this research is the students of the Faculty of Psychology at University of Surabaya grade 2012. Samples who join this research at least 80 students selected by incidental sampling technique. Collecting data using a questionnaire self-efficacy, self-regulated learning, and uses the average value of achivement index (GPA) of students. The research hypothesis is tested using Spearman correlation analysis. The results showed no relationship between self-efficacy and academic achievement (r = 0.234, p = 0.036 < 0.05), and there also no relationship between self-regulated learning and academic achievement (r = 0.072, p = 0.526 > 0.05). From these results it can be concluded that self-efficacy is more having a relationship with academic achievement compared with self-regulated learning. Self-efficacy of 5.4% contributed to academic achievement.